Multivariate optimization of square wave voltammetry using bismuth film electrode to determine atrazine - Bia, Gonzalo Luis (2014)
A rapid and simple square wave voltammetry method (SWV) for atrazine determination with bismuth film electrode using chemometrics was developed. Different variables such as buffer pH and SWV frequency, pulse height and step potential were screened in a 24 full factorial design. The significant variables were optimized by using a central composite design (CCD) combined with desirability function (DF). Optimum conditions were set as follow: buffer pH 2.3, frequency 300 Hz, pulse height 0.09 V and step potential −0.0024 V. Under these optimum conditions the method has a linear response over (1.8–7.5) × 10−6 mol L−1 with detection and quantification limits of 5.9 × 10−7 and 1.8 × 10−6 mol L−1, respectively.